Genotyping a novel Theileria parva candidate vaccine antigen in cattle- and buffalo-derived parasites - Sibeko-Matjila, K.P. (Kgomotso Penelope) (University of Pretoria, 2020)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2019.